(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2019)
The different types of resources like Wood, Timber, bushmeat, medicines etc provided by forests are termed Forest Resourses. A forest is a dense growth of trees and other plants covering a significant amount of land. It is an ecosystem, a community of plants and animals interacting with one another and their environment. Forestry is the science involved in studying, preserving and managing forests. This is a descriptive study. Here, attempt is made to study the natural resources along with its needs and importance. Problems and Conservation of Forest resources are also analysed here.